Antioxidant and neuroprotector effect of Lepidium meyenii (maca) methanol leaf extract against 6-hydroxy dopamine (6-OHDA)-induced toxicity in PC12 cells - Rodríguez-Huamán, Ángel (2017)
Reactive oxygen species (ROS) are normally produced during cell metabolism, there is strong evidence to suggest that ROS produced in excess impair the cell and may be etiologically related to various neurodegenerative diseases. This study was undertaken to examine the effects of Lepidium meyenii (MACA) methanol leaf extract on neurotoxicity in PC12 cell exposed to 6-hydroxydopamine (6-OHDA). Fresh samples of “maca” leaves were processed in order to obtain foliar extracts and to evaluate the neurobiological activity on PC12 cells, subjected to the cytotoxic effect of 6-OHDA through the determination of the capacity antioxidant, cell viability and cytotoxicity assays on PC12 cells. The results of the tests of antioxidant activity, showed maximum values of 2262.37 and 1305.36 expressed in Trolox equivalents (TEAC), for the methanolic and aqueous fractions respectively. Cell viability assays at a dose of 10 μg extract showed an increase of 31% and 60% at 6 and 12 h of pretreatment, respectively. Cytotoxicity assays at the same dose and exposure time showed a 31.4% and 47.8% reduction in lactate dehydrogenase (LDH) activity and an increase in superoxide dismutase (SOD) activity. The results allow us to affirm that the methanolic foliar extract of “maca” presents in vitro neurobiological activity of antioxidant protection, increase in cell viability and reduction of cytotoxicity against oxidative stress generated by 6-OHDA. In conclusion, the present study shows a protective role for Lepidium meyenii leaf extract on 6-OHDA-induced toxicity by an antioxidant effect.